Design and Implementation of 3U CubeSat Platform Architecture - Sua Song; Hongrae Kim; Young-Keun Chang (International Journal of Aerospace Engineering)
This paper describes the main concept and development of a standard platform architecture of 3U Cube Satellite, whose design and performance were implemented and verified through the development of KAUSAT-5 3U CubeSat. The 3U standard platform is built in 1.5U size and developed as a modular concept to add and expand payloads and attitude control actuators to meet the user’s needs. In the case of the electrical power system, the solar panel, the battery, and the deployment mechanism are designed to be configured by the user. Mechanical system design maximizes the electrical capability to accommodate various payloads and to integrate and miniaturize EEE (Electrical, Electronic, and Electromechanical) parts and subsystem functions/performance into limited-size PCBs. The performance of KAUSAT-5 adopting standard platform was verified by mounting the VSCMG (Variable Speed Control Moment Gyro), which is one payload for technical demonstration, at the bottom of the platform and the infrared (IR) camera, which is the other payload for science mission, on the top. The 3U CubeSat equipped with the electronic optical camera is under development implementing the standard platform to reduce development cost and schedule by minimizing additional verification.